KESALAHAN BERBAHASA PADA PAMFLET MEDIA ONLINE PONDOK PESANTREN AL-FATTAH: KAJIAN SINTAKSIS - Nur Aini, Alifia; Putriyani, Hanifah; Laila, Muslikhatul (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This type of qualitative literature study uses reading and note-taking data collection techniques. The aim is to analyze language errors in the writing of Al-Fattah Islamic Boarding School pamphlets. The data used are in the form of phrases, clauses, and sentences contained in the pamphlet. The source of the data used is a document in the form of a pamphlet which has been disseminated by the Al-Fattah Islamic Boarding School media team on social media. The results of the study indicate that there are language errors at the syntactic level, namely (1) sentence errors which include three sentences that are not parallel, one sentence that is not frugal, one sentence that is influenced by a foreign language, four sentences that are wrong in spelling, and one sentence that is ambiguous/taxacious , (2) There is also an error in the field of phrases which includes one excessive use of elements, and one wrong phrase in writing (typo). Keywords: language errors, syntax, pamphlets, online media